Initiation and evaluation of patient counseling centre services to out patients in a tertiary care hospital - S, Ganachari M; W, Tarun; CL, Vimala (Indian Journal of Pharmacy Practice)
Patient counseling is a critical component of the dispensing process, in order to ensure that the patient receives and understands important information such as the name of the drug and the purpose of the medication. Clinical pharmacists are the most qualified health professional to provide counseling to the patients. Physicians due to their heavy patient load, lack of time are unable to spend enough time with the patients and so the pharmacists should take this as their primary responsibility and counsel the patients. The objectives of the study were to initiate a patient counseling centre and to assess the medication adherence and disease knowledge of the patients before and after educating by clinical pharmacist. The study was conducted for a period of 8 months after obtaining Ethics Committee approval. A survey was conducted for health care professionals and a patient counseling centre was initiated in a semi-private room for patient counseling. 104 patients were enrolled as per the inclusion and exclusion criteria. Medication adherence and disease knowledge questionnaires were administered before and after Clinical Pharmacist intervention. 94 patients completed the follow up of the study out of 104 enrolled patients. There was statistically significant improvement (P<0.001) in knowledge level from baseline(7.298) to the follow up(13.691). Comparison of various demographic factors like age, gender, diagnosis and education status showed impact of patient counseling on improvement of overall medication and disease knowledge score. The non-compliance reasons to stop/miss medication as told by patients were 09(30.0%) patients forgetfulness, while 7(23.33%) patients mentioned their fear of side effects, 1(3.33%) patient had confusion in the schedule of taking drugs and 1(3.33%) patient mentioned high cost of drugs as reason for non-adherence. The findings showed of this study showed that a well-structured patient counseling by clinical pharmacist will result in better knowledge of disease and medications which inturn improves their medication adherence.
Keywords: Medication knowledge; Medication adherence; Patient counseling centre; Patient counseling